PERAN MARKETING COMPETENCY DALAM MENINGKATKAN KEUNGGULAN BERSAING - Fatik Rahayu (Universitas Trisakti, 2006)
Functional area competencies are considered as sources of competitive advantage (Porter, 1994; Heene & Stanches, 1997; Cravens, 1996; Vickery el AI, 1993; Vickery et. Al, 1994), and marketing competency is one of them. Marketing competency construct is defined as the sum of the performed on 31 competitive items, weighted by importance and extent of marketing responsibility (Vickery et al., 1994).This study examines a model of relationships between marketing competency and business performance outcomes such as market share and market share growth. The questioners were sent to marketing managers from manufacture organizations at Jakarta. The instrument from Vickery et al. (1994), was used in this study. Regression was used to analysis this data. The result showed that marketing competency is related to business performance outcomes (in this case: market share and market share growth). So, It suggests that marketing competency is a source competitive advantage.Keywords : Marketing Competency, Business Performance Outcomes (market share and market share growth), competitive Advantage.